Influence of magnetic field on electrical and thermal transport in the hole doped ferromagnetic manganite: La0.9Na0.1MnO3. Issue 3 (14th January 2019) - Das, Rajasree; Chanda, Amit; Mahendiran, Ramanathan
Abstract : Magnetic field dependent electrical resistivity ( ρ ), thermal conductivity ( κ ) and thermopower ( S ) of polycrystalline La0.9 Na0.1 MnO3 have been reported and the possible mechanisms are discussed. Abstract : We report the magnetization ( M ), magnetostriction, electrical resistivity ( ρ ), thermal conductivity ( κ ) and thermopower ( S ) of polycrystalline La0.9 Na0.1 MnO3 over a wide temperature range of 5 to 360 K. This sample undergoes a paramagnetic to ferromagnetic transition around T C = 274 K and electrical resistivity ρ shows an insulator–metal transition around T IM = 292 K. The sign of thermopower S is positive in the entire temperature range which indicates that majority charge carriers are holes. Thermopower exhibits a peak and thermal conductivity shows a dip at T C in the absence of magnetic field. Large difference between the experimentally determined activation energies of ρ and S in the insulating state indicates small polaron hopping dominant conduction above T IM . Polaron formation above T C, was further confirmed from the anomaly observed in thermal expansion (Δ L / L 0 ) which shows a change in slope at T IM . In the vicinity of T C at 3 T applied field, magneto-thermopower (∼61.5%) is larger than magnetothermal conductivity (∼12.7%) and magnetoresistance (∼49%).